Xi Jinping's long road to somewhere? China's OBOR initiative and how Europe should respond - Guy De Jonquières (European Centre for International Political Economy (ECIPE), 2016)
The true nature and purpose of China's One Belt One Road (OBOR) initiative are subject to much speculation. The one certainty is that OBOR commands powerful high-level Chinese support and is backed by a large investment of political capital. It is no less than the personal signature initiative of President Xi, who has made clear that he regards it as central to his political legitimacy and as the tangible embodiment of his "China Dream" of rejuvenating the nation and its ruling Communist Party - which in his mind are probably the same thing. However, the initiative faces formidable challenges. It remains unclear how much new investment OBOR has generated, how far it makes economic or geo-political sense or, indeed, how far China can afford to support it, given its current economic and financial difficulties. There has been fierce competition to win government support for OBOR projects but its political nature risks leading to serious misallocation of resources. (...)
Keywords: 330; Volkswirtschaftsplan; Investitionspolitik; Verkehrsinfrastruktur; China